Mice Deficient in Epithelial or Myeloid Cell Iκκβ Have Distinct Colonic Microbiomes and Increased Resistance to Citrobacter rodentium Infection - Mackos, Amy R.; Allen, Jacob M.; Kim, Eunsoo; Ladaika, Chris A.; Gharaibeh, Raad Z.; Moore, Cathy; Parry, Nicola M. A.; Boyaka, Prosper N.; Bailey, Michael T. (Frontiers in Immunology, 2019)
The colonic microenvironment, stemming from microbial, immunologic, stromal, and epithelial factors, serves as an important determinant of the host response to enteric pathogenic colonization. Infection with the enteric bacterial pathogen Citrobacter rodentium elicits a strong mucosal Th1-mediated colitis and monocyte-driven inflammation activated via the classical NF-κB pathway. Research has focused on leukocyte-mediated signaling as the main driver for C. rodentium-induced colitis, however we hypothesize that epithelial cell NF-κB also contributes to the exacerbation of infectious colitis. To test this hypothesis, compartmentalized classical NF-κB defective mice, via the deletion of IKKβ in either intestinal epithelial cells (IKKβΔIEC) or myeloid-derived cells (IKKβΔMY), and wild type (WT) mice were challenged with C. rodentium. Both pathogen colonization and colonic histopathology were significantly reduced in IKKβ-deficient mice compared to WT mice. Interestingly, colonic IL-10, RegIIIγ, TNF-α, and iNOS gene expression were increased in IKKβ-deficient mice in the absence of bacterial challenge. This was associated with increased p52, which is involved with activation of NF-κβ through the alternative pathway. IKKβ-deficient mice also had distinct differences in colonic tissue-associated and luminal microbiome that may confer protection against C. rodentium. Taken together, these data demonstrate that classical NF-κB signaling can lead to enhanced enteric pathogen colonization and resulting colonic histopathology.